Pengaruh Citra Merek, Promosi, dan Harga Terhadap Kepuasan Konsumen (Studi pada Konsumen Sneakers Adidas Mahasiswa Universitas Budi Luhur Angkatan 2021 di Jakarta) - Ami Nabila; Ravindra Safitra Hidayat (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This study aims to determine the effect of brand image, promotion, and price on consumer satisfaction of Adidas sneakers, the method used is quantitative. The data source used in this study is Mahasiwa Budi Luhur Batch 2021. The sample of this study used a non-probability sampling technique with a random sample random sampling method with the Slovin formula and obtained 116 respondents. The results of this study indicate that Brand Image, has a negative and insignificant effect on Customer Satisfaction, while the Promotion variable has a significant effect on customer satisfaction, and the price variable has a significant effect on customer satisfaction. The results of this study are expected to increase customer satisfaction in adidas sneakers.